THE IMPORTANCE OF SOCIAL ACTIVITY IN OLD AGE - Sitora Akbarovna Ikromova (Prospects for innovative technologies in science and education, 2025)
Old age is a period of life that brings profound changes in physical, psychological, and social dimensions. Among the key determinants of well-being in later life, social activity plays a crucial role in maintaining mental health, preventing cognitive decline, and fostering a sense of belonging. This article examines the significance of social engagement for older adults, drawing on research findings in gerontology, psychology, and public health. It highlights the positive effects of active participation in community life, intergenerational relationships, volunteering, and cultural activities on emotional stability and life satisfaction. The discussion also addresses barriers to social participation in old age and strategies to promote inclusive and accessible social environments. The findings suggest that sustained social activity is an essential component of healthy aging and a protective factor against loneliness, depression, and social isolation.